Korpus Arab Pesantren: Digitizing the work of Arabic non-Arabic speakers at Modern Islamic Institution Darussalam Gontor - Yoke Suryadarma; Gamal Abdul Nasir Zakaria (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2022)
Modern Islamic Institution Darussalam Gontor (PMDG) is One of the educational institutions in Indonesia that has been consistent in learning Arabic since its inception due to there are many Arabic works produced by the student community component within the institution. The purpose of this study is to specifically describe the works of non-Arabic Speaker Arabic students and explain the process of collecting and digitizing Arabic corpus data sources made by non-Arabic Speaker Arabic students at Modern Islamic Institution Darussalam Gontor, Ponorogo, East Java. This research employs a field study with a descriptive qualitative analysis approach as a research method. The results reveal that, first, the works of Arabic language students based on the type of data can be categorized into two parts, namely written Arabic works (written products) and spoken Arabic works (Spoken Products). Conventional written data can be read by software and conventional data cannot be read. Second, the process of collecting and digitizing Arabic corpus data by Arabic non-Arabic Speaker students at Modern Islamic Institution Darussalam Gontor was carried out in three stages. The first stage converts the conventional data in the form of handwriting and voice recordings to digital data in *doc format. The second stage is the conversion of digital data in *doc format into plain text (*txt) format. The third stage is to enter data in *txt format into a web-based data processing engine, namely Sketch Engine. Thus, the digital corpus data is ready to be processed into a study based on certain linguistic objectives.